SPR965, a Dual PI3K/mTOR Inhibitor, as a Targeted Therapy in Ovarian Cancer - Tran, Arthur-Quan; Sullivan, Stephanie A.; Chan, Leo Li-Ying; Yin, Yajie; Sun, Wenchuan; Fang, Ziwei; Dugar, Sundeep; Zhou, Chunxiao; Bae-Jump, Victoria (Frontiers in Oncology, 2021)
SPR965 is an inhibitor of PI3K and mTOR C1/C2 and has demonstrated anti-tumorigenic activity in a variety of solid tumors. We sought to determine the effects of SPR965 on cell proliferation and tumor growth in human serous ovarian cancer cell lines and a transgenic mouse model of high grade serous ovarian cancer (K18-gT121+/−;p53fl/fl;Brca1fl/fl; KpB model) and identify the underlying mechanisms by which SPR965 inhibits cell and tumor growth. SPR965 showed marked anti-proliferative activity by causing cell cycle arrest and inducing cellular stress in ovarian cancer cells. Treatment with SPR965 significantly inhibited tumor growth in KpB mice, accompanied by downregulation of Ki67 and VEGF and upregulation of Bip expression in ovarian tumors. SPR965 also inhibited adhesion and invasion through induction of the epithelial–mesenchymal transition process. As expected, downregulation of phosphorylation of AKT and S6 was observed in SPR965-treated ovarian cancer cells and tumors. Our results suggest that SPR965 has significant anti-tumorigenic effects in serous ovarian cancer in vitro and in vivo. Thus, SPR965 should be evaluated as a promising targeted agent in future clinical trials of ovarian cancer.